PENGARUH ROLLING MASSAGE PUNGGUNG DENGAN PIJAT MARMET TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS - Rika Ruspita; Dwi Yulina Wati; Lisviarose (LPPM Universitas Abdurrab, 2026)
Breast milk is a primary source of nutrition that plays a crucial role in supporting optimal infant growth and development. Smooth breast milk production in postpartum mothers is influenced by various physiological and psychological factors; therefore, effective interventions are needed to enhance the lactation process. One non-pharmacological approach involves the use of back rolling massage and Marmet massage, which work by stimulating the hormones prolactin and oxytocin. This study aimed to analyze the effect of back rolling massage and Marmet massage on increasing breast milk production among postpartum mothers at the Independent Midwifery Practice of Rosita, S.Tr.Keb. A quantitative method was employed using a quasi-experimental design with a two-group pretest-posttest approach. The study was conducted from May to July 2024, with a population consisting of all mothers who gave birth at the practice. The sample comprised 16 respondents selected via purposive sampling. Data collection utilized observation sheets, while analysis was performed using univariate and bivariate methods, specifically the Wilcoxon test. The results indicated that prior to the intervention, all respondents experienced issues with smooth breast milk production. Following the intervention, an increase in breast milk production was observed in 93.8% of respondents in the back rolling massage group and 87.5% in the Marmet massage group. Statistical analysis yielded a p-value of 0.000 (p<0.05), indicating a significant effect of back rolling massage and Marmet massage on increasing breast milk production in postpartum mothers. The study concludes that back rolling massage and Marmet massage are effective non-pharmacological interventions for enhancing breast milk production in postpartum mothers.